Tear Secretion and Ferning Patterns Among Premature and Full-Term Newborns - Beden, U.; Turgut-Çoban, D.; Aygün, C.; Ulu-Güngör, I.; Süllü, Y.; Erkan, D.; Küçüködük, Ş. (Turkish J Pediatrics, 2008)
In this study, we aimed to assess the quality and quantity of tears among premature and term newborns. Tear ferning and Schirmer's tests were conducted over the first 10 days of life. Correlations between tear ferning patterns, Schirmer's scores, post-conceptional age, and birth weight were evaluated. Forty-six newborns (23 preterm, 23 term) were enrolled, with a mean post-conceptional age of 36.6 weeks and a mean weight of 2598.2 g. Mean total, basal and reflex Schirmer's test results were 13.5 mm, 6.7 mm and 6.8 mm, on the right and 14.0 mm, 7.1 m, and 6.9 mm on the left eye, respectively. Median ferning score was 2 (range 1-3) bilaterally. Schirmer scores were correlated with ferning capacity and post-conceptional age. Our study shows that newborns secrete moderate quantity, good quality tears. Ferning capacity, Schirmer scores and post-conceptional age are correlated.
Keywords: Ferning; Newborn; Premature; Schirmer; Tear Secretion